Biomass and composition of Atlantic menhaden schools in winter on the continental shelf offshore of New Jersey: Application of a novel hydroacoustic survey with midwater trawl sampling - Geneviève Nesslage; James Gartland; Robert J. Latour; Christopher Gurshin; Dong Liang; Dustin Gregg; Stefan Axelsson; Leif Axelsson; Wayne Reichle; Jeff Kaelin; J. Michael Jech; Ray Mroch; et al. (Fisheries Research, 2026)

Examining the impacts of spatial closures in the Gulf Menhaden fishery - Robert T. Leaf; Wei Wu; Ray M. Mroch; Robert Trigg; David Duval (Frontiers in Marine Science, 2025)
Policymakers in the northern Gulf of America have proposed various spatial closures in recent years as a management tool for the Gulf Menhaden Brevoortia patronus fishery. In this work, we aim to understand how the seasonal movement of the stock will impact the efficacy of spatial restrictions by examining the short-term impacts of simulated area closures of 1.6, 3.2, and 4.8 km adjacent to land on the commercial Gulf Menhaden fishery using commercial logbook data from 2006 to 2009 and 2011. We used bootstrap resampling (n = 1,000) of trip-level data to describe five descriptive metrics. These were the mean set-specific catch per unit effort (CPUE, metric tons, mt set -1 ), the mean number of sets deployed on each trip, the mean trip-specific CPUE (mt minute -1 ), the median distance (km) traveled to the first set, and the median distance (km) traveled among subsequent sets (for trips with at least two sets). We explored the impacts of closures by comparing the month-specific distributions of the descriptive metrics from all trips to those calculated using only those trips with all sets outside of a particular restricted area. Using the simulation, we evaluated the resulting spatial differences in fishing effort that would occur. The results of the simulation indicated that, in all restriction scenarios for all months, the spatial restrictions served to increase the travel distance to the first set and to reduce the mean number of sets taken. Set-specific and trip-specific CPUE are reduced in the restriction scenarios. We found that the reduction of total harvest (mt) for the 1.6 km restriction regime was 4.3 to 7.2%, 9.1 to 12.0% in the 3.2 km restriction regime, and 12.7 to 15.4% in the 4.8 km restriction regime. This work provides information about the impacts on the fishery that result from area closures. Such information is necessary to evaluate the efficacy and impacts of spatial closures for the Gulf Menhaden fishery.

Socio-economic impacts and responses of the fishing industry and fishery managers to changes in small pelagic fish distribution and abundance - Felipe J. Quezada-Escalona; Desiree Tommasi; Isaac C. Kaplan; Pierre-Yves Hernvann; Timothy H. Frawley; Dorleta Garcia; Leire Ibaibarriaga; Sonia Sánchez-Maroño; Carryn de Moor; Jennifer Beckensteiner; Amy M. Schueller; Diana Feijó; et al. (Reviews in Fish Biology and Fisheries, 2025)
Small Pelagic Fish (SPF) exhibit large fluctuations in abundance and distribution in response to environmental variability. To maintain the resilience of fishing communities and develop effective and equitable climate adaptation strategies, improved understanding of how the fishing industry responds to spatio-temporal shifts within and across SPF populations is of critical importance. In this paper, we examine the responses of the fishing industry and resource managers to shifts in SPF availability worldwide and identify the resulting socioeconomic impacts. Leveraging SPF case studies from around the globe, we synthesize and compare the social-ecological linkages and feedbacks mediating how SPF fisheries respond to changes in marine ecosystem structure and function associated with (1) spatial shifts in species distribution and habitat availability, (2) ‘boom and bust’ population dynamics, or (3) changes in fish size and quality. Our case studies illustrate multiple paths towards the resilience of small pelagic fisheries and the fishing industry dependent upon them while emphasizing the need for increased coordination and cooperation across sectors and scales as climate change progresses. Drawing from the lessons offered by historical responses, as environmental variability increases, efforts to increase the flexibility and dynamism of SPF harvest portfolios and management strategies, licensing regimes, and international catch and allocation agreements may be required to ensure resource sustainability and human well-being.

The Path to an Ecosystem Approach for Forage Fish Management: A Case Study of Atlantic Menhaden - Kristen A. Anstead; Katie Drew; David Chagaris; Amy M. Schueller; Jason E. McNamee; Andre Buchheister; Geneviève Nesslage; Jim H. Uphoff Jr.; Michael J. Wilberg; Alexei Sharov; Micah J. Dean; Jeffrey Brust; et al. (Frontiers in Marine Science, 2021)
Atlantic menhaden ( Brevoortia tyrannus ) support the largest fishery by volume on the United States East Coast, while also playing an important role as a forage species. Managers’ and stakeholders’ increasing concerns about the impact of Atlantic menhaden harvest on ecosystem processes led to an evolution in the assessment and management of this species from a purely single-species approach to an ecosystem approach. The first coastwide stock assessment of Atlantic menhaden for management used a single-species virtual population analysis (VPA). Subsequent assessments used a forward projecting statistical catch-at-age framework that incorporated estimates of predation mortality from a multispecies VPA while analytical efforts continued toward the development of ecosystem models and explicit ecological reference points (ERPs) for Atlantic menhaden. As an interim step while ecosystem models were being developed, a series of ad hoc measures to preserve Atlantic menhaden biomass for predators were used by managers. In August 2020, the Atlantic States Marine Fisheries Commission formally adopted an ecological modeling framework as a tool to set reference points and harvest limits for the Atlantic menhaden that considers their role as a forage fish. This is the first example of a quantitative ecosystem approach to setting reference points on the United States Atlantic Coast and it represents a significant advance for forage fish management. This case study reviews the history of Atlantic menhaden stock assessments and management, outlines the progress on the current implementation of ERPs for this species, and highlights future research and management needs to improve and expand ecosystem-based fisheries management.